Impact of climate change on potato productivity in Uttar Pradesh and adaptation strategies - Dua, V K; Singh, B P; Kumar, Sushil; Lal, S S (Potato Journal, 2016)
Present study was carried out to assess the impact of climate change on potato productivity in Uttar Pradesh, using WOrld FOod STudies crop growth simulation model. Three potato cultivars belonging to three different maturity groups were used (Kufri Badshah – late maturing, Kufri Bahar – medium maturing and Kufri Pukhraj – early maturing). The analysis was done for baseline scenario (2000) and for future climate scenarios of the years 2020 and 2055 using A1FI scenario of temperature (SRES A1FI pathway) and atmospheric CO2 (based on the Bern-CC model for A1FI scenario). Potential production of potato cultivars was estimated for 61 different locations across Uttar Pradesh. The data generated through model were interpolated using kriging technique and thematic maps were generated on potential productivity in 2000 and changes thereon in future climates. Under baseline scenario, the mean productivity of Kufri Badshah, Kufri Bahar and Kufri Pukhraj was 46.0, 46.8 and 45.3 t/ha, respectively. Although the increase in CO2 concentration alone is expected to bring an increase of 4.0 - 4.5% in productivity in 2020 and 17.0 -19.5% in 2055, the corresponding increase in temperature is likely to decrease the mean productivity by 8.5-10.4% and 17.7-27.5% in 2020 and 2055, respectively. Overall, under the combined impact of increased CO2 and temperature, the model has projected a decline in productivity of Kufri Badshah, Kufri Bahar and Kufri Pukhraj to the tune of 5.5, 6.1 and 7.0%, respectively in 2020 and 9.4, 10.9 and 13.4%, respectively in 2055 without adaptation.